Natural radioactivity and radiocesium in perch (Perca fluviatilis) - Piñero García, Francisco (University of Gothenburg, 2022)
Activity concentration of natural radioactivity (238U, 234U, 226Ra, 210Po) and 137Cs in organs and tissue of wild European perch from lake Fiolen and lake Fysingen. The activity is showed in Bq/kg in fresh weight.

The samples of European perch (Perca fluviatilis) consisted of 39 individuals caught in Lake Fiolen and 95 individuals caught in Lake Fysingen during 2020. The sample collection was performed by the Swedish Museum of Natural History and the samples were provided as a loan from their sample bank Environmental Specimen Bank.

The data consists of the mean measurements of the radioactive elements in different anatomical regions of the perch samples. Cesium-137 content could not be measured in the fins of the samples from Lake Fysingen, resulting in a missing value.

The data is available as an Excel file and as a semicolon-separated .csv.

Aktivitetskoncentration av naturlig radioaktivitet (238U, 234U, 226Ra, 210Po) och 137Cs i organ och vävnader hos vild europeisk abborre från insjöarna Fiolen och Fysingen. Aktiviteten visas i Bq/kg i färskvikt.

Proverna av aborre (Perca fluviatilis) utgjordes av 39 individer infångade i Fiolen och 95 individer infångade i Fysingen under 2020. Insamlingen gjordes av Naturhistoriska riksmuséet och proverna har lånats ur Miljöprovbanken.

Datasammanställningen består av det uppmätta medelvärdet av de radioaktiva ämnena i olika anatomiska regioner av aborrproverna. För proverna från Fysingen var det inte möjligt att uppmäta Cesium-137 i fenorna och detta medelvärde saknas därför i dataunderlaget.

Data finns tillgänglig i Excel-format och som semikolonseparerad .csv.
Naturligt radioaktiva ämnen och cesium i abborre (Perca fluviatilis)
Keywords: RADIOACTIVE ELEMENTS; PERCH-LIKE FISHES; cesium 137; polonium 210; radium 226; uranium 234; uranium 238; Radioactivity; radioaktivitet; Environmental Sciences; Miljövetenskap; Fish and Aquacultural Science; Fisk- och akvakulturforskning; Biota; Biologi och ekologi; Environment; Miljö; Inland Waters; Sjöar och vattendrag